2019
DOI: 10.1111/labr.12145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Wages: The Role of Personal Interactions and Job Selection

Abstract: We estimate the effects of obesity on wages accounting for the endogenous selection of workers into jobs requiring different levels of personal interactions in the workplace. Using data from the National Longitudinal Survey of Youth 1979 combined with detailed information about occupation characteristics from O*Net, we confirm the results from the literature finding a wage penalty for obese White women. This penalty is higher in jobs that require a high level of personal interactions. Accounting for job select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Obesity is not only associated with a number of health conditions (Calle & Thun, 2004;Hossain et al, 2007), studies have also shown that it is associated with weaker labor market outcomes (Baum & Ford, 2004;Caliendo & Lee, 2013;Cawley, 2004;Deb et al, 2011;Pagan & Davila, 1997). Most of the literature agrees that the negative impacts of obesity on labor outcomes are more prevalent amongst females (Averett & Korenmann, 1996;Bhattacharya & Bundorf, 2009;Caliendo & Lee, 2013;Mason, 2012;Moro et al, 2019;Pagan & Davila, 1997). However, some have found obesity is negatively associated with labor outcomes for both genders (Baum & Ford, 2004;Morris, 2007;Rooth, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is not only associated with a number of health conditions (Calle & Thun, 2004;Hossain et al, 2007), studies have also shown that it is associated with weaker labor market outcomes (Baum & Ford, 2004;Caliendo & Lee, 2013;Cawley, 2004;Deb et al, 2011;Pagan & Davila, 1997). Most of the literature agrees that the negative impacts of obesity on labor outcomes are more prevalent amongst females (Averett & Korenmann, 1996;Bhattacharya & Bundorf, 2009;Caliendo & Lee, 2013;Mason, 2012;Moro et al, 2019;Pagan & Davila, 1997). However, some have found obesity is negatively associated with labor outcomes for both genders (Baum & Ford, 2004;Morris, 2007;Rooth, 2009).…”
Section: Introductionmentioning
confidence: 99%